The relationship between platelet-lymphocyte ratio (plr) and mortality of sepsis patients in the intensive care unit of Waled Regional General Hospital in 2020-2023 - Khairunnisa Purwati; Donny Prasetyo Priyatmoko; Isti Noviani (Institute of Computer Science (IOCS), 2026)
Background: Sepsis is one of the leading causes of mortality worldwide, especially in patients treated in intensive care units. This condition is characterized by organ dysfunction due to a systemic inflammatory response to infection that can lead to death if not treated promptly. Platelet-Lymphocyte Ratio (PLR) is a simple inflammatory marker that can provide information about sepsis mortality. PLR is calculated by dividing the platelet count by the absolute lymphocyte count. Objective: This study aims to analyze the relationship between PLR and mortality of sepsis patients in the Intensive Care Unit of Waled Regional General Hospital (RSUD Waled) in 2020-2023. Methods: This study used an analytical method with a cross-sectional design. Data were obtained through medical records with a sample size of 65 people and the data collection method was total sampling. Data analysis used the Fisher Exact Test. Results: Most sepsis patients had high PLR values, with 52 patients dying, and sepsis patients with low PLR values, with 10 patients surviving and 3 patients dying. The results of data analysis using the Fisher's Exact test showed a p-value of <0.001. Conclusion: There is a significant relationship between PLR and mortality of sepsis patients in the Intensive Care Unit of Waled Regional Hospital.